2018
DOI: 10.1016/j.wear.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A new test method to simulate low-severity wear conditions experienced by rubber tire materials

Abstract: An innovative rotary tribometer was developed in order to reproduce the abrasive wear of reinforced rubber materials for tire. The device allows performing accelerated, quantitative friction and wear tests which mimic real usage conditions in terms of kinematics and dynamics of the contact, temperature and open cycle conditions, specifically in low severity conditions, which often represent a challenge to mimic and study. The specific point emphasized here is the strong impact of wear debris accumulated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, not all of them are used during the measurement of particles which have formed during the wear of tires. Some of this methods were shown in the research of Xiang et al 71,72 The application of the CPC (Condensation Particle Counter) and the atomizer is limited to the [57][58][59][60][61] detection of particles whose size is 5 nm, while more reliable measurement of smaller particles can be conducted by filters. In each case, the most influential parameter on the sampling accuracy was the flow rate, so all of this should be taken in the consideration during the future researches.…”
Section: Methods For Measuring the Wear Of Tiresmentioning
confidence: 99%
“…However, not all of them are used during the measurement of particles which have formed during the wear of tires. Some of this methods were shown in the research of Xiang et al 71,72 The application of the CPC (Condensation Particle Counter) and the atomizer is limited to the [57][58][59][60][61] detection of particles whose size is 5 nm, while more reliable measurement of smaller particles can be conducted by filters. In each case, the most influential parameter on the sampling accuracy was the flow rate, so all of this should be taken in the consideration during the future researches.…”
Section: Methods For Measuring the Wear Of Tiresmentioning
confidence: 99%
“…According to the stress-strain of rubber materials in experimental tests, as shown in Figure 4, the fitting coefficient C 10 and C 01 of the cord thread glue, apex, and sidewall rubber can be obtained. 21,22 The rubber materials and characteristic parameters of the running wheel are shown in Tables 1 and 2.…”
Section: Constitutive Model For Running Wheel Tirementioning
confidence: 99%
“…There are so many studies relative to the sliding wear of rubber composites. [12][13][14][15][16] Dong et al [17] has investigated the tribological properties of nitrile butadiene rubber affected by aging processes and the main wear mechanism was fatigue wear under sliding conditions. Similarly, because the wear resistance of pure rubber materials is very limited in engineering applications, Lin et al [18] has studied tribological properties of SBR/BR rubber composites reinforced with graphene and cellulose nanocrystal (CNC) under dry sliding conditions, it was found that the friction and wear properties of the rubber composites strongly depend on the normal load and sliding velocity.…”
Section: Introductionmentioning
confidence: 99%